Regulating the Construction Services Supervisory Board Based on the Principle of Legal Certainty - Jeffry Yuliyanto Waisapi; Slamet Suhartono; Yovita Arie Mangesti; Rosalinda Elsina Latumahina (Dinasti Research, 2025)
Corruption in Indonesia's construction sector results in material losses and damaged public trust, and slows economic growth. To address this problem, systemic reforms focusing on tender transparency, strict law enforcement, and strengthening oversight institutions are needed. Law No. 2/2017 on Construction Services provides a comprehensive legal framework, but its implementation is often hampered by a lack of inter-agency coordination and weaknesses in supervision and enforcement. This research uses a normative method to analyze regulations related to construction supervision and design a conceptual framework and policy recommendations to improve the effectiveness of supervision. The results show that legal certainty and transparency are key to building public trust and ensuring accountability. The implementation of regulations such as Government Regulation No. 22/2020 and Minister of Public Works and Housing Regulation No. 7/PRT/M/2019, accompanied by consistent sanctions, strengthens trust in the legal and supervisory systems. Systematic supervision and transparent reporting are essential elements to maintain the integrity and effectiveness of construction projects.